S01-1 Addressing challenges in the role of work on health. (1st September 2016) - Seixas, Noah; Peckham, Trevor; Hajat, Anjum; Baker, Marissa
Abstract : The nature of work has, and continues to undergo radical transformation, with significant changes in work organisation, especially through 'fissuring' of business models, increased globalisation, including expansion of international supply chains and large scale immigration, and the blurring of lines between what constitutes work and non-work exposures. The conceptual model of occupational health that was developed in the 'OSHA' era is largely inadequate for addressing these changes. The major elements of these changes, and their implications for preventing work-related injury and illness are discussed. Informing this discussion is the rapidly expanding disparities in both wealth and health, typically associated race, gender, nativity, education and other elements of SES. Although highly intertwined with these factors, the role of work in creating the associated health and wealth disparities is rarely explicitly discussed. An alternative model of worker health and health disparities, describing the interaction of social determinants of health and work-related risks is proposed, and used to generate discussion about future directions for occupational health research and prevention activities.